2020
DOI: 10.3758/s13423-020-01722-x
|View full text |Cite
|
Sign up to set email alerts
|

Ignored visual context does not induce latent learning

Abstract: People usually become faster at finding a visual target after repeated exposure to the same search display. This effect, known as contextual cueing, is often thought to rely on a highly efficient learning mechanism, relatively unconstrained by the availability of attentional resources. Consistent with this view, experimental evidence suggests that contextual cueing can be found even when participants are instructed to ignore the repeated visual context, although this learning remains latent until the context r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
1
20
3
Order By: Relevance
“…Applied to the current work, the learning of the task-irrelevant context could not be blocked under fast presentation because attention was directed to both the task-relevant and -irrelevant contexts. Moreover, these results are also with the suggestion by Vadillo et al (2020) that previous studies underestimated the importance of selective attention in contextual cueing (Jiang and Chun, 2001;Jiang and Leung, 2005). For instance, it demonstrates that attentional selection is important for contextual learning; however, task requirements determine which level of perceptual learning can be achieved.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Applied to the current work, the learning of the task-irrelevant context could not be blocked under fast presentation because attention was directed to both the task-relevant and -irrelevant contexts. Moreover, these results are also with the suggestion by Vadillo et al (2020) that previous studies underestimated the importance of selective attention in contextual cueing (Jiang and Chun, 2001;Jiang and Leung, 2005). For instance, it demonstrates that attentional selection is important for contextual learning; however, task requirements determine which level of perceptual learning can be achieved.…”
Section: Discussionsupporting
confidence: 86%
“…Jiang and Leung (2005) concluded that the expression of learned contextual regularities requires selective attention, while the build-up of these memories (i.e., contextual learning) does not. However, this idea was further developed by Vadillo et al (2020) when they reevaluated the role of selective attention in contextual cueing. The study employed a similar design to Jiang and Leung (2005) with a larger sample size and showed that no latent learning would be possible without selective attention.…”
Section: Introductionmentioning
confidence: 99%
“…Vadillo, Konstantinidis, and Shanks (2016) showed that participants are aware of the repeated displays when sufficiently sensitive measures of awareness are used in high-powered experiments. Travis, Mattingley, and Dux (2013) and Vadillo, Giménez-Fernández, Aivar, and Cubillas (2020) found that contextual cuing is not completely independent of working memory or selective attention. Finally, Luque, Vadillo, López, Alonso, and Shanks (2017) showed that contextual cuing is flexible and can be modified in a goal-directed way when participants are instructed to search for another target.…”
Section: Discussionmentioning
confidence: 99%
“…The novel context on the other hand was used as a control condition, in which distractor locations were determined randomly in every trial and their spatial locations could not predict the target location. It has been widely shown that search speed in the repeated context is faster than novel context (e.g., Chun andJiang, 1998, 1999;Zheng and Pollmann, 2019;Vadillo et al, 2020b), leading to the suggestions that participants, through repeated encounters of old displays, form some incidental memory about the invariant spatial target-distractor relations in these displays, with this spatial context memory subsequently guiding selective attention more effectively towards the target location. Chun and Phelps (1999) proposed that context memory stores spatial/configural or more general relational information, independent of whether or not this information is acquired implicitly or explicitly.…”
Section: Introductionmentioning
confidence: 99%